The safety and efficacy of the fissure-first approach in lung segmentectomy for patients with incomplete fissures - Zhu, Shu-Sheng; Zheng, Jianan; Chen, Liang; Zhu, Quan; Wen, Wei; Zhu, Jian; Wang, Jun (Frontiers in Oncology, 2024)
Background Lung segmentectomy has gained much more attention as an important surgical method for treating early-stage lung cancer. However, incomplete fissures increase the difficulty of lung segmentectomy. The aim of this study was to analyze the safety and efficacy of the fissure-first approach in precision resection of lung segments for patients with incomplete fissures. Methods The clinical data of patients with incomplete fissures who underwent lung segmentectomy were retrospectively analyzed. Date was divided into fissure-first approach in lung segmentectomy group (group A) and fissure-last approach in lung segmentectomy group (group B). The general linear data, operation times, intraoperative adverse events, postoperative recovery dates and complications were compared. Results A total of 122 patients with complete clinical data were included. Patients in group B had more COPD (p < 0.05), and the lesions in group A were more closely related to the hilum of the lung (p < 0.05). Compared to Group B, Group A achieved better surgical outcomes, such as operation time, postoperative hospital stays, intraoperative bleeding, number of intrapulmonary lymph nodes sampled, counts of resected subsegments (except the upper lobe of the right lung), and rate of conversion to thoracotomy (all p < 0.05). Conclusion The fissure-first approach is a safe and effective surgical approach in lung segmentectomy for patients with incomplete fissures. This approach can reduce the counts of resected subsegments and improve techniques in lung segmentectomy for patients with lung incomplete fissures.